Twentieth-Century Philosophy of Religion The History of Western Philosophy of Religion, Volume 5. - Oppy, Graham Robert; Trakakis, N. N. (Hoboken : Taylor and Francis, 2014)
The twentieth century saw religion challenged by the rise of science and secularism, a confrontation which resulted in an astonishingly diverse range of philosophical views about religion and religious belief. Many of the major philosophers of the twentieth century - James, Bergson, Russell, Wittgenstein, Ayer, Heidegger, and Derrida - significantly engaged with religious thought. Idiosyncratic thinkers, such as Whitehead, Levinas and Weil, further contributed to the extraordinary diversity of philosophical investigation of religion across the century. In their turn, leading theologians an.
23. Richard Swinburne24. Late-Twentieth-Century Atheism; Chronology; Bibliography; Index
Description based upon print version of record.
Keywords: Religion -- Philosophy -- History -- 20th century; RELIGION / Philosophy; Electronic books